Purification, crystallization and Patterson search of haemoglobin IV from the armoured catfish Liposarcus anisitsi - Delatorre, P.; Smarra, ALS; Fadel, V; Canduri, F.; Dellamano, M.; Bonilla-Rodriguez, G. O.; de Azevedo, W. F. (Munksgaard Int Publ Ltd, 2001)
Considerable interest is currently focused on fish haemoglobins in order to identify the structural basis for their diversity of functional behaviour. The armored catfish Liposarcus anisitsi presents accesorial air breathing through a modified stomach, which allows this species to survive in waters with low oxygen content. The analysis of its haemolysate has shown the presence of four main haemoglobins, with this work focusing on haemoglobin IV (LaHb-IV). LaHb-IV was crystallized and X-ray diffraction data were collected to 2.4 Angstrom resolution using a synchrotron-radiation source. The crystal belongs to the orthorhombic space group P2(1)2(1)2(1), with unit-cell parameters a = 52.6 (1), b = 104.8 (2), c = 113.9 (2) Angstrom; preliminary structural analysis revealed the presence of one tetramer in the asymmetric unit. The structure was determined using the standard molecular-replacement technique.